The Difference Between Righ-Brain and Left-Brain Dominance on Reading Achievement - Zumrotul Faizah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT : This final project is a quantitative research design in this study, the researcher limit discussion by stating the following research problem: “Is there any diferences between Right-brain and left-brain dominance on reading students achievement?”. The aim of this study is to find out the most dominance used by students in learning reading and to find out whether or not a effect between right-brain and left-brain on reading achievement. The result of this study can help teacher’s metode in teaching reading. The subject of this study was the students of English Depatment class of the second semester. The sample of this research was 74 students. The data were collected using a questionnaire 5-Likert scale and reading test. The data were analyzed using independentt-test through SPSS 22.0 version. The result of this research showed that the finding that the effect between right-brain and left-brain dominance on reading achievement is positive result means that there is difference between right-brain and left brain dominance on reading achievement. The level sig. (2 tailed) was greater than the level of significant (.00< 0.05), then H0 was rejected H1 was accepted. It can be said that all students of English Department use left-brain dominance in learning English especially reading skill. Meaning that the students who use left-brain dominance have good score and students who lowest score also use right-brain dominance but it is not suitable with them. These finding imply that student who learn language with left-brain dominance it will be good in achievement then who learn with the other brain dominance.The researcher suggested applying the brain dominanceprovided to overcome their difficulties. However, this research was expected to be developed by the future researchers who had the same interest. Key Words: Right-brain dominance, Left-brain dominance, Reading achievement